The Substantive University Action and the Integration with the Environment: The Case of the Chorotega Regional Campus of the National University of Costa Rica - Suárez Serrano, Andrea (2018)
We reviewed the university extension and research projects of the Chorotega Regional Campus (SRCH) of the National University of Costa Rica (UNA) to strengthen the interrelation between extension, research, and teaching and their integration with the region. The objective of this paper is to analyze how the university extension and research projects influence the internal and external integration of SRCH to accomplish the activities of the substantive university action. Twenty-eight extension and research projects were reviewed; SRCH ran them from 2012 to 2017. The review was conducted using a qualitative and exploratory meta-analysis of the projects recorded in the UNA Academic Information System. The extension-research projects have encouraged a strong integration of UNA with communities and strategic allies, expanding the knowledge of diverse disciplines. The projects allow professors to improve their interaction and collaboration with social organizations, public institutions, and international peers. However, it is also necessary to review the regionalization policies to facilitate a greater integration with the private sector and other universities. The regional grant funds are essential to develop extension-research projects. Without such grants, the outreach of the regional campuses will be drastically reduced.